Sodium butyrate attenuated iE‐DAP induced inflammatory response in the mammary glands of dairy goats fed high‐concentrate diet. (2nd September 2020) - Wang, Yan; Liu, Jing; Huang, Jie; Chang, Guangjun; Roy, Animesh Chandra; Gao, Qianyun; Cheng, Xiaoye; Shen, Xiangzhen
Abstract: BACKGROUND: Long‐term high‐concentrate (HC) diet feeding increased bacterial endotoxins, which translocated into the mammary glands of dairy goats and induced inflammatory response. γ ‐d ‐Glutamyl‐ meso ‐diaminopimelic acid (iE‐DAP), bacterial peptidoglycan component, triggered inflammatory response through activating nucleotide oligomerization domain protein 1 (NOD1) signaling pathway. While dietary supplemented with sodium butyrate (SB) relieved inflammatory response and improved animal health and production. To investigate the effects and the mechanisms of action of SB on the inflammatory response in the mammary glands of dairy goats fed HC diet, 12 Saanen dairy goats were randomly assigned into HC group and SB regulated (BHC) group. RESULTS: The results showed that SB supplementation attenuated ruminal pH decrease caused by HC diet in dairy goats resulting in a decrease of proinflammatory cytokines and iE‐DAP plasma concentration and the mRNA expression of NOD1 and other inflammation‐related genes. The protein levels of NOD1, NF‐κB p65 and NF‐κB pp65 were decreased by the SB supplementation. The expression of histone deacetylase 3 (HDAC3) was also inhibited by the SB supplementation. Meanwhile, the chromatin compaction ratios and DNA methylation levels of NOD1 and receptor‐interacting protein 2 (RIP2) of BHC group were upregulated. CONCLUSION: Collectively, the SB supplementation mitigated the inflammatory response in the mammary glands of dairy goats during HC‐induced subacute ruminal acidosis (SARA) by inhibiting the activation of the NOD1/NF‐κB signaling pathway through the decrease of the iE‐DAP concentration in the rumen fluid and plasma and HDAC3 expression. DNA methylation and chromatin remodeling also contributed to the anti‐inflammatory effect of SB. © 2020 Society of Chemical Industry